Development of cellulose based food-ink from cellulose powder - N.Y, Azman; S.F.Z.M, Fuzi; N.H., Abdul Manas (2024)
Three-dimensional or 3D printing studies utilizing biopolymer, a digital manufacturing technology acting as additive manufacturing, have gained global attention, particularly in the food industries. However, the utilization of cellulose powder to create food ink for 3D printing is relatively recent. Therefore, this study aimed to prepare cellulose-based food ink, analysed using carboxymethyl cellulose powder (CMC) through rheology and thermal analysis. The formulated cellulose-based food ink from carboxymethyl cellulose powder underwent examination through rheology, thermogravimetric analysis (TGA), and Fourier -transformed infrared spectroscopy (FTIR). The results showed shear-thinning behaviour for rheology properties and the presence of the hydroxyl group (–OH stretching), C–H stretching vibration and ether groups (–O– stretching), which was excellent for 3D printing. The amount of CMC powder used in the food ink formulation was increased due to the higher thermal stability of the food ink as determined by the TGA. This discovery is applicable to 3D printing in the food industry since CMC powder exhibits shear thinning behaviour at low concentrations and has stable thermal characteristics comparable to printable and edible materials.